Workflow Scheduling Mechanism Using PCSO n Cloud: Case Study - Chaturvedi, Prachi; Sharma, Sanjiv (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing has emerged as a service model that enables on-demand network get right of entry to a massive number of available virtualized resources and applications with a minimal management attempt and a minor rate. The unfold of Cloud Computing technology allowed handling complicated applications together with Scientific Workflows, which consists of a set of extensive computational and data manipulation operations. Cloud Computing enables such Workflows to dynamically provision compute and storage assets necessary for the execution of its responsibilities way to the pliancy asset of those assets. However, the dynamic nature of the Cloud incurs new challenges, as a few allocated assets may be overloaded or out of get entry to all through the execution of the Workflow. Moreover, for data extensive responsibilities, the allocation strategy have to keep in mind the facts placement constraints on the grounds that facts transmission time can growth extensively in this example which implicates the growth of the general of completion time and value of the Workflow. Likewise, for in depth computational responsibilities, the allocation strategy must consider the form of the allocated digital machines, greater specifically its CPU, reminiscence and network capacities. Yet, an essential venture is the way to correctly schedule the Workflow obligations on Cloud resources to optimize its ordinary best of provider. In this paper, we endorse a QoS aware algorithm for Scientific Workflows scheduling that objectives to enhance the overall quality of service (QoS) with the aid of considering the metrics of execution time, data transmission time, price, sources availability and facts placement constraints. We prolonged the Parallel Cat Swarm Optimization (PCSO) algorithm to put in force our proposed method. We tested our algorithm inside pattern Workflows of various scales and we compared the consequences to the ones given by the same old PSO, the CSO and the PCSO algorithms. The consequences display that our proposed algorithm improves the general satisfactory of provider of the tested Workflows.